An Atypical Case of Oral Squamous Cell Carcinoma of Mandibular Alveolus - Seba Abraham; Bhagyalekshmi Mallika; Arunima Reshma; ReejaMol Mohammed Kassim (Case Reports in Dentistry)
Oral squamous cell carcinoma is the most common type of oral malignant neoplasm. As per literature, squamous cell carcinomas of the alveolar ridge account for 9% of all the oral carcinomas. The oral squamous cell carcinoma shares clinical similarity with various forms of inflammatory gingival lesions and is often misdiagnosed in our routine dental practice. The dentist should have precise knowledge regarding the clinical manifestation of this deadly disease as early diagnosis and prompt treatment can reduce morbidity and mortality of the disease.